Personal information: perceptions, types and evolution - Saglam, Rahime Belen; Nurse, Jason R. C.; Hodges, Duncan (Elsevier, 2022)
Advances in technology have made us as a society think more about cyber security and privacy, particularly how we consider and protect personal information. Such developments have introduced a temporal dimension to the definition of personal information and we have also witnessed new types of data emerging (e.g., phone sensor data, stress level measurements). These rapid technological changes introduce several challenges as legislation is often inadequate, and therefore questions regularly arise pertaining whether information should be considered personal or sensitive and thereby better protected. In this paper, therefore, we look to significantly advance research into this domain by investigating how personal information is regarded in governmental legislations/regulations, privacy policies of applications, and academic research articles. Through an assessment of how personal information has evolved and is perceived differently (e.g., in the context of sensitivity) across these key stakeholders, this work contributes to the understanding of the fundamental disconnects present and also the social implications of new technologies. Furthermore, we introduce a series of novel taxonomies of personal information which can significantly support and help guide how researchers and practitioners work with, or develop tools to protect, such information.
Keywords: Personal information; Information sensitivity; Data protection; Regulations; Taxonomy; Cyber security